2014
DOI: 10.1130/g36033.1
|View full text |Cite
|
Sign up to set email alerts
|

From continent to intra-oceanic arc: Zircon xenocrysts record the crustal evolution of the Solomon island arc

Abstract: The fi rst U-Pb ages from a ca. 26-24 Ma pluton on Guadalcanal, in the intra-oceanic Solomon island arc (southwest Pacifi c Ocean), reveal Eocene-to Archean-aged zircon xenocrysts. Xenocryst populations at ca. 39-33 Ma and ca. 71-63 Ma correlate with previously obtained ages of supra-subduction magmatism within the arc. A ca. 96 Ma zircon population may be derived from Cretaceous ophiolite basement crust or region-wide continental rift-related magmatism. Xenocryst age populations alternate with periods of ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Indeed, continental fragments in the overriding plate do not necessarily modify the geochemical signature of arc magmatism. This has been demonstrated, for example, in the Solomon Island and Vanuatu (Figure a), where Precambrian and Paleozoic inherited zircons within arc magmatic rocks are indicative of the existence of continental basements, but the geochemistry of these rocks is characteristic of a Mariana‐type island arc with a negligible contribution of continental materials [ Buys et al ., ; Tapster et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, continental fragments in the overriding plate do not necessarily modify the geochemical signature of arc magmatism. This has been demonstrated, for example, in the Solomon Island and Vanuatu (Figure a), where Precambrian and Paleozoic inherited zircons within arc magmatic rocks are indicative of the existence of continental basements, but the geochemistry of these rocks is characteristic of a Mariana‐type island arc with a negligible contribution of continental materials [ Buys et al ., ; Tapster et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The map highlights Permian to Triassic lithostratigraphic units in Australia (Gympie terrane), New Caledonia (Teremba Terrane), and New Zealand (Brook Street, Murihiku, and Dun Mountain‐Maitai terranes). Star indicates the locations of possible Australian‐derived continental fragments [ Mortimer et al ., ; Buys et al ., ; Tapster et al ., ]. (b) Simplified geological map of the New England Orogen and the Gympie terrane [after Glen and Roberts , ].…”
Section: Introductionmentioning
confidence: 99%
“…Closure of the Tetagouche backarc basin during the Salinic orogenic cycle telescoped and rejoined rocks of the Popelogan arc with those of the backarc basin ; separation of the remnants of the two tectonic systems is not always clear because igneous rocks with backarc characteristics are locally closely associated with arc magmatic rocks (Winchester and van Staal, 1994;Schulz and Ayuso, 2003;Hussey et al, 2010). Building on the tectonic analyses of van Staal et al (2009) and Reusch and , this work better defines 1) and presents additional evidence that this arc was built on a continental ribbon rifted from the leading edge of Ganderia rather than on oceanic crust, a setting that may also be more common for several oceanic arcs in the southwest Pacific (e.g., Falloon et al, 2014;Tapster et al, 2014). Ganderia is one of the major accreted continental crustal fragments in the Northern Appalachians and forms basement to most of New Brunswick and Maine ( Fig.…”
Section: Introductionmentioning
confidence: 67%
“…The presence of continental fragments within the intra-oceanic arc structure was demonstrated recently under the example of two modern island arcs (Buys et al, 2014;Tapster et al, 2014). It has been suggested that these fragments have been rifted and transported thousands of kilometres away from the source continent (Buys et al, 2014).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Another possibility could be the influence of old continental crust fragments present in the basement of the intra-oceanic arc, a scenario that has recently been shown in modern intra-oceanic arcs of Vanuatu (Buys et al, 2014) and the Solomon Islands (Tapster et al, 2014). The remnants of older crustal fragments in these two settings has been demonstrated by the presence of old Archean zircons.…”
Section: Implication For Geodynamic Developmentmentioning
confidence: 99%